A15 A PROSPECTIVE, NON-INFERIORITY, MULTI-CENTER, RANDOMIZED TRIAL COMPARING COLONOSCOPY VS ORAL CAPSULE DELIVERED FECAL MICROBIOTA TRANSPLANTATION (FMT) FOR RECURRENT CLOSTRIDIUM DIFFICILE INFECTION (RCDI). (1st March 2018) - Kao, D H; Roach, B; Silva, M; Beck, P; Rioux, K P; Madsen, K; Goodman, K; Xu, H; Chang, H; Louie, T
Abstract: Background: FMT is highly effective in the treatment of RCDI. Delivery of FMT by upper route and lower routes has been utilized, achieving cure rate of at least 80%. However, the ideal route of delivering FMT has not been determined. Aims: To compare 1) the cure rate of RCDI; 2) safety; 3) patient satisfaction, preference and changes in quality of life between capsule vs colonoscopy delivered FMT. Methods: Adult patients who had at least 3 documented episodes of CDI were randomized to FMT administered by either capsule or colonoscopy at 1:1 ratio. Key exclusion criteria included severe and complicated CDI; inflammatory bowel disease (IBD), unless stable symptoms for ≥ 3 months; dysphagia. Seven volunteer stool donors provided stool for FMT. Results: 116 patients (57 in capsule and 59 in colonoscopy arm) were randomized between Oct 2014 - Aug 2016 in Edmonton and Calgary. Participant baseline characteristics were shown in Table 1. The cure rate of RCDI was 96.2% in the capsule arm and 95.9% in the colonoscopy arm after a single FMT (non-inferiority p value <0.0001, Fig 1). One patient in each group died of underlying cardiopulmonary disease within 12 weeks of treatment, unrelated to FMT. Minor adverse events (AE) (abdominal discomfort, nausea, vomiting) were less frequent in capsule arm (12.5% vs 5.4%, p= 0.321). Significant improvement in quality of life measured by SF-36 occurred following FMT with no difference between groups (p>0.5). The proportion of patients rating treatment "not at all unpleasant" was higher in the capsule arm (67%; 95% CI:56–78%) than the colonoscopy arm (44%; 95% CI: 31–59%). Conclusions: FMT administered by capsules was as efficacious as colonoscopy. No serious AE attributable to FMT was identified with either delivery modality. Fewer minor AEs were seen with capsule. Both FMT delivery methods improved quality of life, but fewer patients found capsule to be an unpleasant treatment modality. Funding Agencies: Alberta Health Services